KARAKTERISTIK FISIK DAN SENSORIS SALAD DRESSING DARI TEPUNG DAN PATI GANYONG TERMODIFIKASI KIMIA - Iffah Muflihati; Nayla Maghfiroh Amalia (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Salad dressing is a type of food that is usually used as a complementary ingredient (sauce) for salads belonging to the emulsion dressing group. Phase separation often occurs during emulsion storage, the stabilizing agent plays an important role in maintaining the stability of the emulsion in salad dressing products. The presence of starch in salad dressings serves as a gelling agent, binder, thickener, emulsifier, and stabilizer. The use of canna tubers in Indonesia is still limited. Canna flour and starch can be modified to develop the desired functional properties. Based on the potential application of modified starch, it is necessary to modify flour and canna starch so that it can be used as a stabilizing agent. The objective of this study was to determine the physical and sensory characteristics of salad dressing from acetylated and crosslinking modified canna flour and starch. The results showed that the application of chemically modified canna flour and starch as a stabilizing agent affected the physical and sensory characteristics of the resulting salad dressing. Modification of acetylation and crosslinking was able to maintain the pH value and emulsion stability during 30 days of storage. Modified canna flour and starch can improve the appearance of the resulting salad dressing. The panelists' preference value was highest on salad dressing samples that used acetylated canna starch as a stabilizing agent. Modification of canna starch by crosslinking and acetylation can be applied as a stabilizing agent in salad dressings. Keywords: acetylation, crosslinking, canna, salad dressing, stabilizing agent